Prices versus quantities: Comparing economic efficiency of feed-in tariff and renewable portfolio standard in promoting renewable electricity generation - Choi, Gobong; Huh, Sung-Yoon; Heo, Eunnyeong; Lee, Chul-Yong (Energy policy, 2018)
In order to promote renewable electricity generation, several countries have been adopting a feed-in tariff (FIT) or a renewable portfolio standard (RPS). Of these two renewable energy policies, investigating which one has better performance is a subject of debate. This study comparatively analyzes the economic efficiency of FIT and RPS in the South Korean renewable energy market. FIT was implemented from 2002 to 2011, while RPS has been in force since 2012; hence, a comparative analysis of the two policies is ideal. The benefit cost ratio and net present value were measured from two different perspectives: the government and energy producers. The results showed that RPS was more efficient for photovoltaic energy from the government's perspective, whereas FIT, for non-photovoltaic energy, such as wind power, bio-energy, and fuel cells. However, from the energy producers’ perspective, FIT was more efficient for photovoltaic energy, while RPS was more efficient for non-photovoltaic energy. •FIT and RPS are compared with respect to South Korean renewable energy policies.•CBA is conducted to assess whether FIT or RPS is more economically efficient.•The study was conducted using two perspectives: government and energy producers.•RPS benefits government for photovoltaic, and FIT for non-photovoltaic energy.